2021
DOI: 10.1101/2021.05.10.442986
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex-Specific Function and Morphology of the Anterior Cruciate Ligament During Skeletal Growth in a Porcine Model

Abstract: Pediatric anterior cruciate ligament (ACL) injuries are on the rise, and females experience higher ACL injury risk than males during adolescence. Studies in skeletally immature patients indicate differences in ACL size and joint laxity between males and females after the onset of adolescence. However, functional data regarding the ACL and its anteromedial and posterolateral bundles in the pediatric population remain rare. Therefore, this study uses a porcine model to investigate the sex-specific morphology and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The median T2* relaxation time was calculated for each ACL bundle. Additionally, the volume of each segmented tissue was recorded, and the cross-sectional area (CSA) of the AM and PL bundles, the complete ACL, MCL, and LCL were calculated as previously described (17,18).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The median T2* relaxation time was calculated for each ACL bundle. Additionally, the volume of each segmented tissue was recorded, and the cross-sectional area (CSA) of the AM and PL bundles, the complete ACL, MCL, and LCL were calculated as previously described (17,18).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Specifically, a study in adult patients reported similar joint stability after isolated AM and PL bundle injuries (11), while a study in pediatric patients reported better outcomes for AM bundle injuries (16). Furthermore, in a skeletally immature pig model, the biomechanical function of the AM and PL bundles of the ACL depends on age and sex, such that the AM bundle plays a larger functional role in older versus younger subjects and males compared to females (17,18). Since evidence regarding treatment of bundle-specific partial injuries in children and adolescents is sparse, there is a need for further investigation of long-term outcomes and degenerative changes in skeletally immature subjects.…”
Section: Introductionmentioning
confidence: 99%